Status-seeking in hedonic games with heterogeneous players - Emiliya Lazarova; Dinko Dimitrov (Fondazione Eni Enrico Mattei (FEEM), 2010)
We study hedonic games with heterogeneous player types that reflect her nationality, ethnic background, or skill type. Agents' preferences are dictated by status-seeking where status can be either local or global. The two dimensions of status define the two components of a generalized constant elasticity of substitution utility function. In this setting, we characterize the core as a function of the utility's parameter values and show that in all cases the corresponding cores are non-empty. We further discuss the core stable outcomes in terms of their segregating versus integrating properties.
Keywords: C78; J41; D71; 330; Coalitions; Core; Stability; Status-seeking